The Effect of Brand Ambassador and Tagline on Brand Awareness on Sr12 Skin Care Products - Supriyadi Supriyadi; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (International Journal of Education, Information Technology, and Others, 2022)
This study aims to: To determine the effect of Brand Ambassador on Brand Awareness on Sr12 Skin Care products, a study in the Purwakarta Village Community, Purwakarta District, Cilegon City. To determine the effect of the Tagline on Brand Awareness on Sr12 Skin Care products, a study was conducted in the Purwakarta Village Community, Purwakarta District, Cilegon City. To determine the effect of Brand Ambassador and Tagline simultaneously on Brand Awareness on Sr12 Skin Care products, a study was conducted in the Purwakarta Village Community, Purwakarta District, Cilegon City. The research method used in this study used a survey method, while the target in this study were Sr12 skincare consumers in Indonesia Purwakarta Village, Purwakarta District, Cilegon City.with an unlimited population. The number of samples determined by this research amounted to 88 people according to Maholtra's opinion. Based on the results of the research "The Effect of Brand Ambassadors and Taglines on Brand Awareness in Sr12 Skin Care Products (study on the Purwakarta Village Community, Purwakarta District, Cilegon City)" can be seen as follows: T test results (partial) for Brand Ambassador tcount result 2.012 > 1.988 t table answers the first hypothesis, namely Brand Ambassador has a significant effect onBrand Awareness sr12 skincare Purwakarta Village, Purwakarta District, Cilegon City. For the Tagline variable hypothesis tcount 4.993 > ttable 1.988, this answers the second hypothesis, namely Tagline has a significant effect on Brand Awareness sr12 skincare Purwakarta Village, Purwakarta District, Cilegon City. Based on the distribution table F table F table = F (k; nk) (2; 88-2) at level a 5% and F table 3.09 so F 22.044 > 3.09 that it is concluded that Ho is rejected Ha is accepted which means Brand Ambassador and Tagline have a positive and significant influence simultaneously on Brand Awareness.